CAPITAL ADEQUACY (SOLVENCY) AND LIQUIDITY RISK MANAGEMENT: ANALYSIS, EVALUATION, AND POSSIBILITIES FOR IMPROVEMENT - Žuk-Butkuvienė, Aleksandra; Vaitulevičienė, Dalia; Staroselskaja, Julija (Ekonomika, 2014)
Abstract. The main purpose of the present research is to analyse the supervision, capital adequacy (solvency) and liquidity prudential norms, limits and requirements of commercial banks operating in Lithuania, as well as to assess the quality of capital adequacy and liquidity risk management impact on the banking industry. The paper consists of two main parts: the analysis of literature and legislation, and the research, its results, recommendations, and conclusions. The first part reviews the theoretical analysis of the level of banking supervision and capital adequacy, liquidity prudential standards value. The authors have examined the banks’ supervising authorities and the regulation of their activities. There were are presented prudential standards of capital adequacy and liquidity for banks operating in Lithuania, their values’change after the Basel III reforms, and the scientific opinion about their development and tightening standards. The authors have carried out a study of the analysis of capital adequacy and liquidity prudential requirements, their evaluation and possibilities for improvement in banks operating in Lithuania. The analysis consists of the assessment of assets and liabilities of banks ensuring the prudential standards depending on the type of risk. The research revealed that the most important in banks’ capital adequacy and liquidity risk management is quality control and the harmonization of bank assets and liabilities. Besides, it is offered to review the calculation of requirements and procedures, to impose additional limits to ensure the basic standards and an efficient banking security. Key words: commercial banks, supervision, liquidity and capital adequacy (solvency) rates, qualitative and quantitative analysis, evaluation